Statistical Analysis on the Effect of Treatment on Blood Pressure Before and After Treatment in General Hospital Takum Using Paired T-Test - Jude, Iroka; Akpienbi, Isaac Oritsejubemi (Darul Yasin Al Sys, 2024)
Hypertension is a preval_ent health condition worldwide, posing a significant risk for cardiovascular diseases. This study investigates the effect of treatment on blood pressure in individuals with hypertension, aiming to compare blood pressure levels before and after treatment, eval_uate the effectiveness of different treatment modalities, and assess the impact of treatment on other health outcomes. A quasi-experimental design is utilized, with participants recruited through convenience sampling. Data on blood pressure measurements are collected from medical records, and descriptive statistics and paired t-tests are used for data analysis. The results indicate a significant decrease in blood pressure levels after treatment, supporting the effectiveness of lifestyle modifications and pharmacological interventions in managing, emphasizing the importance of early detection and individualized treatment plans. Future research should focus on exploring the long-term effect of treatment and optimizing treatment strategies for specific patient populations.